Effect of Environmental Factors on Seed Germination and Early Seedling Emergence of Carolina geranium (Geranium carolinianum) - LIU,X. (2018)
ABSTRACT: Carolina geranium (Geranium carolinianum) is an emerging invasive weed in rape and wheat fields in China. A better understanding of its germination and emergence ecology will enable the development of integrated weed control strategies. In this study, we investigated the effects of temperature, photoperiod, soil water content, salinity, and burial depth, on germination and emergence of Carolina geranium. Germination percentages were over 74% under 15/20 and 20/25 oC night/day temperature regimes. Germination rate was independent of light/dark regime. Increasing salinity reduced germination of Carolina geranium from 81.1% at 0 mM to 0% at 160 mM NaCl. Seeds germination was peaked at 50% soil moisture, but was completely inhibited at < 20% and > 90%. The seedling emergence above 82.2% was observed when seeds were placed at a depth from 0 to 1 cm, and no seedlings emerged from seeds placed at a depth of 7 cm. Current work provide the basic information to effectively prevent and control this invasive weed in Chinese rape and wheat fields.